Adaptive Performance in Early Career Transitions The Role of Learning Goal Orientation A Systematic Literature Review - Ayu Ambarwati; Ilham Arief; Ardi Ardi; Khoe Yao Tung (Cv. Syntax Corporation Indonesia, 2026)
Adaptive performance is a critical competency for employees navigating rapidly changing organizational environments; however, its theoretical foundations during early career transitions, particularly in government settings, remain underdeveloped. Following the PRISMA 2020 guidelines, this systematic review aimed to identify, synthesize, and evaluate evidence on adaptive performance during early career transitions, with a focus on learning goal orientation as an antecedent, career adaptability as a mediating resource, and the contextual influences of identity threat and bureaucratic structures within the public sector. Searches of Scopus and Semantic Scholar using the search string ((